PSEUDOMORPHIC LINES OF AUTOCHTHONOUS GRANITOIDS - SVIESHNIKOV, K.; KOSTENKO, N.; LYSAK, A.; HASANOV, Yu.; KADURIN, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
It was shown the existence of six pseudomorphic lines for autochthonous ultrametamorphic granitoids: leukogranitic, alaskitic, kinzigitic, plagiogranitic, dioritic and enderbitic. The petrochemical peculiarities of each line are discussed. It was shown that main features of lines depend on the ratio Al2O3/CaO, which consistently decreases from the beginning to the end of this sequence. That allows to regard the given sequence as systematic.